Legal Devices To Manage Customary Maori Land: Overcoming The Conflict Between Retention And Development - Kingi, Tanira T; Maughan, C William (Journal of Malaysian and Comparative Law, 2019)
The management of customary Maori land is a key factor in the economic development of Maori people. Development of Maori land with the restriction that the land be retained in Maori ownership seems plausible enough but problems arise, where land is both an economic resource to be used efficiently and also the identity and well of spirituality for its owners.